Rowing against the current: Diversification in Africa's resource-rich economies - John M. Page (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The exploitation of natural resources is a huge opportunity, but one that carries considerable risks. Relative prices in resource-exporting economies tend to push them towards economic structures dominated by the resource sector. This paper explores ways to achieve diversification in a resource-rich economy. It describes the relative price changes that accompany a resource boom and suggests policies and public investments to mitigate their impact. It explores some of the issues that influence the participation of local firms in the resource value chain and argues for broadening the options for diversification, through the development of "industries without smokestacks" and investments in knowledge.
Keywords: Q32; Q38; O25; O14; L71; F23; 330; diversification; knowledge; local content; natural resources; tradable services